Determination of Cirrus Occurrence and Distribution Characteristics Over the Tibetan Plateau Based on the SWOP Campaign. Issue 8 (14th April 2023) - Yang, Zhen; Li, Dan; Luo, Jiali; Tian, Wenshou; Bai, Zhixuan; Li, Qian; Zhang, Jinqiang; Wang, Haoyue; Zheng, Xiangdong; Vömel, Holger; Wienhold, Frank G.; Peter, Thomas; et al.
Abstract: Balloon sounding with the Compact Optical Backscatter Aerosol Detector (COBALD) and Frost Point hygrometers (FPs) provides in situ data for a better understanding of the vertical distribution of cirrus clouds. In this study, eight summer balloon‐borne measurements in Kunming (2012, 2014, 2015, and 2017) and Lhasa (2013, 2016, 2018, and 2020) over the Tibetan Plateau were used to show the distribution characteristics of cirrus clouds. Differences of cirrus occurrence were compared by different indices: the backscatter ratio (BSR) at a 455 nm/940 nm wavelength (BSR455  > 1.2/BSR940  > 2), the color index (CI > 7), and the relative humidity with respect to ice (RHice  > 70%). Analysis of the profiles indicated that BSR455  > 1.2 was the optimal criterion to identify the cirrus layer and depict the distribution of the CI and RHice within cirrus clouds. The results showed that the median CI (RHice ) within the cirrus clouds at both sites was mostly in the 18–20 (90%–110%) range at pressures below 120 hPa. Furthermore, the balloon‐borne measurements combined with Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) measurements indicated a high frequency of cirrus occurrence near the tropopause in Kunming and Lhasa. The top height of cirrus occurrence at both sites was above the cold point tropopause and the lapse rate tropopause. Both Kunming and Lhasa had the highest frequency of thin cirrus clouds in the 0–0.4 km vertical cirrus thickness range. Plain Language Summary: Balloon‐borne measurements of cirrus clouds are scarce over the Tibetan Plateau. The sounding water vapor, ozone, and particles (SWOP) campaign has collected Compact Optical Backscatter Aerosol Detector (COBALD) and Frost Point Hygrometers (FPs) data for eight summers in Kunming and Lhasa. The backscatter ratio at wavelengths of 455 and 940 nm (BSR455, BSR940 ) from COBALD, the color index (CI), and the relative humidity over ice (RHice ) from the FPs are able to indicate the occurrence of cirrus clouds. BSR455 >1.2/BSR940  > 2 was the optimal criterion to identify the cirrus layer in the upper troposphere over the Tibetan Plateau. The results showed that the CI and RHice within the cirrus clouds at both sites have a consistent distribution. The median CI (RHice ) remained essentially in the range of 18–20 (90%–110%) below 120 hPa. The top height of cirrus occurrence at both sites was above the cold point tropopause and the lapse rate tropopause. Thin cirrus clouds (less than 400 m thick) had the highest frequency in both Kunming and Lhasa. Key Points: A backscatter ratio over 1.2/2 at a 455 nm/940 nm wavelength can effectively identify cirrus clouds over the Tibetan Plateau Cirrus clouds were observed above the cold point tropopause (CPT) in both Kunming and Lhasa About 38% (39%) of the cirrus clouds are thinner than 400 m in Kunming (Lhasa)